Detailed Investigations on the Solid Cell Culture and Antimicrobial Activities of the IranianArnebia euchroma. (27th June 2011) - Haghbeen, K.; Pourmolaei, S.; Mareftjo, M. J.; Mousavi, A.; Akbari Noghabi, K.; Hosseini Shirazi, F.; Meshkat, A.
Abstract : In pursuit of strong shikalkin-producing cell lines, seeds of the Iranian Arnebia euchroma were collected from Dena altitudes in the central Zagross. Chemical analysis showed that the dried root of the plant contained about 8.5% (w/w) shikalkin pigment. The root explants of the young plantlets, obtained from the germinated seeds, were used for establishing callus. Then, parameters effective on proliferation and pigment production of the resulting calli were studied in detail. Accordingly, two modified media called mLS and mM9 were optimized for propagation and pigment production, respectively. Using these media, the biomass of the A.euchroma calli was increased to 600%, and the pigment production reached to a maximum of 16.3 mg per gram of the wet biomass in a period of a subculture (21 days). Parallel to these experiments, the antimicrobial activity of shikalkin pigment was examined on some fungi and Gram-positive and Gram-negative bacteria. Results indicated that the pigment was almost ineffective on fungi and Gram-negative bacteria, but it was meaningfully effective against Micrococcus luteus .